2023
DOI: 10.14791/btrt.2023.0012
|View full text |Cite
|
Sign up to set email alerts
|

Supramaximal Resection for Glioblastoma: Redefining the Extent of Resection Criteria and Its Impact on Survival

Abstract: Glioblastomas (GBMs) are the most common and aggressive primary brain tumors, and despite advances in treatment, prognosis remains poor. The extent of resection has been widely recognized as a key factor affecting survival outcomes in GBM patients. The surgical principle of “maximal safe resection” has been widely applied to balance tumor removal and neurological function preservation. Historically, T1-contrast enhanced (T1CE) extent of resection has been the focus of research; however, the “supramaximal resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Maximum safe resection has been interpreted differently by different surgeons, leading to definitions of resection extent that have been handled inconsistently in clinical practice ( 88 ). A key operationalization of maximum safe resection is gross total resection, commonly understood as the complete removal of the contrast-enhancing tumor mass.…”
Section: Treating Gliomamentioning
confidence: 99%
See 2 more Smart Citations
“…Maximum safe resection has been interpreted differently by different surgeons, leading to definitions of resection extent that have been handled inconsistently in clinical practice ( 88 ). A key operationalization of maximum safe resection is gross total resection, commonly understood as the complete removal of the contrast-enhancing tumor mass.…”
Section: Treating Gliomamentioning
confidence: 99%
“…Resection beyond the CE tumor, termed “supratotal” or “supramaximal” resection, has become an active field of research in the last decade, based on the premise that removing non-contrast enhancing tumor or even tissue appearing normal on magnetic resonance imaging (MRI) would capture residual tumors ( 82 , 88 ). The currently available evidence on the benefits and outcomes associated with supramaximal resection remains mixed.…”
Section: Treating Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“… 56 , 57 Depending on the physiology of the tumour and the location, a range of studies have shown that SMR significantly improves PFS and OS of patients, compared to those that underwent GTR or partial resection surgery. 58 , 59 Other novel surgical procedures that improves GTR and prevents surgery‐associated complications involve using intraoperative imagining such as MRI or ultrasound for real‐time visualisation of the tumour region, fluorophores such as sodium fluorescein (SF) and 5‐aminolevulinic acid (5‐ALA), dyes that bind to proteins in the blood at the tumour site (SF fluorophore) or metabolised by cancer cells (5‐ALA fluorophore), which can be detected under ultraviolent light and the use of motor evoked action potentials in real‐time to help monitor vital regions of the brain that are involved in motor functions. These innovative procedures have shown significant improvements in GTR and survival rates in adults as compared to surgery alone.…”
Section: Current Management Of Paediatric‐type Diffuse High‐grade Ast...mentioning
confidence: 99%